THE EFFECTIVENESS OF TIKTOK-BASED MEDIA IN IMPROVING STUDENTS’ PUBLIC SPEAKING SKILLS - Muhammad Farih Ridwan; A.Samsul Ma'arif; Ali Maksum (UIN Maulana Malik Ibrahim Malang, 2026)
This study aims to improve the public speaking skills (maharah kalam) of PKPBA students at UIN Malang, Faculty of Tarbiyah and Teacher Training, through the utilization of TikTok as a learning medium. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 30 students. The instruments included a speaking assessment rubric, observation sheets, and student perception questionnaires. The findings revealed a significant improvement in students’ public speaking skills. The percentage of students categorized as “Excellent” increased from 26.67% in Cycle I to 50% in Cycle II. Moreover, positive student perceptions toward TikTok as a learning medium increased from 80% to 93.33%. These findings indicate that integrating TikTok with pedagogical strategies such as model videos, pair practice, and structured feedback effectively enhances students’ fluency, confidence, and creativity in speaking Arabic. Therefore, TikTok can serve as an innovative and relevant alternative medium for teaching maharah kalam in the digital era.